Lima Barreto e a delatação das mazelas de Clara dos Anjos (1948) - Muller, Ana Carolina Carvalho (Universidade Federal do Tocantins, 2023)
The purpose of this article is a discussion of the use of literature as a source for historical research. Using the book Clara dos Anjos (1948) by Lima Barreto as a source, we will analyze the representation of women developed in the selected material. This article is divided into three parts: in the first chapter, we analyze Lima Barreto's life in order to contextualize this novel, since his works were exceptionally influenced by the course of his life. The second part is a theoretical discussion of the literary genre and the possibilities of approximation to historical reality for the purposes of research. And finally, we will analyze the above-mentioned work, focusing on the representation of women constructed by the author, especially on all the injustice suffered by lower-class women that Lima Barreto is able to highlight.